Estimation of Beach Profile Changes after Monsoon in the Mai Khao Beach - Suteerasak, Thongchai; Limsakul, Wadcharawadee; Koedsin, Werapong (KKU Science Journal, 2023)
This research was conducted to preliminarily survey the surface condition and changes in beach profiles of the Mai Khao beach, Phuket Province, before and after the monsoon season of the year 2021. The information obtained was considered for choosing an area that was suitable for tracking coastal erosion problems leading to the change in Mai Khao beach area. Ten measurement stations were set up and monitored by the local people and the local government. The data collection of x y z coordinates was done using TOPCON Electronic Total Station camera. The collected data were then used to create 3D model of beach profile of each area. Moreover, the slope value of the beach was calculated to study the beach profile change. The results showed that the surface condition of some areas were changed due to the erosion of the waterway that flowed into the sea. In addition, the average slope value of the beach decreased from the first area to the final area and the decrease in slope value of the beach occurred in a period of monsoon season. However, there have five areas that should be monitored and tracked beach surface due to erosion in the area.